The Attributes of Knowledge Worker as Prime Movers in Public Organizations - Roosehaziram Mohd Rahim, Em; Farik Mat Yatin, Saiful; Aidid Adil Zainal, Muhammad; Mizan Taib, Khairul; Mohamed, Bunyamin (International Journal of Engineering and Technology, 2018)
Civics Department in public sector of Malaysia has a major responsibility in ensuring that Malaysians instilled with the spirit of patriotism and moral values and aspirations of the nation for preparing Malaysia to achieve developed nation by 2020. With the goal to achieve its vision as a Leader of National Patriotism, a special task force known as Tenaga Penggerak (TP) has been created. This task force acts as a driver to achieve the mission by delivering excellence patriotism program through education, training, awareness and strategic partnerships. TP also have the objective to improve the knowledge and understanding of patriotism and statehood, government policies, current issues, and appreciation of moral values. TP also can be known as knowledge worker in this department based on its responsibilities and main critical success factor of every planned activities and to achieve the objective. This paper proposes positive approach to maintain the quality knowledge worker in Civics Department in instilling patriotism and statehood of Malaysian citizen.Â Â